ANALISIS KEBUTUHAN LEMBAR KERJA MAHASISWA MATERI KESETIMBANGAN UAP CAIR PADA SISTEM BINAIR BERBASIS GREEN CHEMISTRY - Herliani, Firmalia; Sanjaya, Sanjaya (Penerbit Lafadz Jaya, 2025)
Practical learning plays an essential role in enhancing students’ understanding of chemistry concepts through direct laboratory experience. This study aims to analyze the needs for developing a Student Worksheet (LKM) based on green chemistry principles for the binary liquid-vapor equilibrium material in Physical Chemistry I practicum. A descriptive qualitative method was employed to explore students’ perceptions, difficulties, and real needs regarding instructional materials. The research population consisted of Chemistry Education students at Sriwijaya University who had completed the practicum, with 66 students, one lecturer, and one laboratory technician as purposive samples. Data were collected via online questionnaires and semi-structured interviews, then analyzed using descriptive percentage and thematic analysis. Results show students have high enthusiasm but face challenges in understanding complex concepts and data interpretation related to the equilibrium material. While most students are aware of green chemistry principles, current instructional materials inadequately incorporate these principles. All respondents agreed on the urgency to develop practical, structured LKM integrated with green chemistry to improve conceptual comprehension, laboratory safety, and sustainable learning. The conclusion highlights a gap between knowledge and practice, calling for innovative instructional design to foster safer and environmentally friendly laboratory education.